The Development of Health Promotion Programs Based on the Smart Application of Students at Lishui University - Yan, Feng; Promthep, Kreeta; Duangkam, Jakrin (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: This research is of critical significance as it addresses the growing concern of physical health among university students by leveraging cutting-edge information technologies to develop and evaluate smart application monitoring to enhance physical health in students at Lishui University. The program utilizes cutting-edge information technologies such as big data analytics, wearable smart devices, the Internet of Things (IoT), and advanced algorithms to monitor and assess students’ physical health comprehensively. The research encompasses a wide range of activities, from the design of the “Lishui University students’ physical health smart monitoring platform” to the collection and analysis of data through surveys, physical fitness tests, and data analysis methods. Materials and Methods: The sample included 400 students from Lishui University. In the first semester of 2024. Stratified into an experimental group and a control group. Each group consisted of 200 students, with an equal gender distribution. The participants were selected through a random sampling method. Research tools are used on the smart application monitoring platform and for physical health testing. In data analysis, including means, standard deviations, and paired t-tests. Results: The results of the study were as follows: After the experiment, the average physical health score of students in the experimental group was significantly higher than that of students in the control group at the 0.05 significance level. Conclusion: In this study, smart application monitoring can effectively promote the physical health of students at Lishui University.